Implementasi Tradisi Grebeg Besar terhadap Pembelajaran IPS pada Siswa Kelas IV SD Negeri Kadilangu 1 Demak - Reskinda Ramandani; Silvy Anjani; Ramdhani Alifatus Saidah; Sayyidatul Munnah; Syafira Ashna Putri Nuha; Ika Oktavianti (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This type of research is field study research. It is very easy to analyze data, especially when it comes to data collection and analysis. The subject of this research is the Great Grebeg Tradition. The findings of this research indicate that Grebeg Besar is a custom of the people of the Regency to commemorate Eid al-Adha in the month of Djulhijjah. This shows that Grebeg Besar is a sacred tradition that has ceremonial significance because gradually the people of Demak and its surroundings are starting to understand its meaning. Data collection methods such as observation, interviews and documentation will be used to carry out this research. The results of this research describe the reality of the Grebeg tradition which is significant and related to religion, leadership, mutual cooperation, aesthetics and economics. This research can be used as a social studies learning resource based on community wisdom for character building which is applied in Class IV of SD Negeri Kadilagu 1.